(untitled) (MAUSAM, 2024)
The metropolis Jakarta is a place where floods often occur which are detrimental to both property and life. Weather forecast information released by Meteorology, Climatology, and Geophysical Agency (BMKG) has very important in anticipating this disaster. Hence, it is important to pay attention to the weather forecast accuracy. The purpose of this study was to examine the effect of variations accuracy in rain events of the Jakarta area includes Central Jakarta, East Jakarta, West Jakarta, North Jakarta, South Jakarta, Bekasi, Tangerang, Depok, and Bogor as known Jabotabek. School of Meteorology Climatology and Geophysics or STMKG Weather Care developed voluntary observations of weather conditions especially rain events. Respondents filled out the form whether there was rain in the location where they lived and would be evaluated using the dichotomous method. This study shows the accuracy of rain prediction in the Jabotabek area of 66.8%, with prediction failures generally is an overestimation. The highest number of correct predictions occurred when the location was not raining. Moreover, the best accuracy is in Bekasi City and South Jakarta and West Jakarta is the worst. The evaluation confirms that it is not easy to predict rain events in a detailed location and the prediction terms used.